The Visual Function Classification System: Translation, Validity, and Reliability of the Persian Version for Individuals with Cerebral Palsy: Persian version of Visual Function Classification System - pashmdarfard, marzieh; Amini, malek; hejazi shirmard, mahnaz; zamiran, sara; Baranello, Giovanni; akbarzadeh baghban, alireza; kalantari, minoo (Iranian Journal of Child Neurology, 2025)
Objectives: This study aimed to translate and develop the Persian version of The Visual Function Classification System (P-VFCS) while assessing its validity and reliability Materials & Methods: The VFCS was created to classify visual function among individuals with Cerebral Palsy (CP). Until this point, no such classification system was available in Iran. Therefore, the VFCS underwent translation into Persian, with the original developer approving the back-translation. A panel of ten occupational therapists and ten parents evaluated the face validity. The Persian version of VFCS (P-VFCS) was administered to 156 participants with CP, aged 1 to 19 years (age range: 2 to 18 years; mean age: 9.1 years; standard deviation: 6.32 years). Inter-rater reliability was measured among 156 parents and four occupational therapists. Test-retest reliability was evaluated throughout two to four weeks with 77 parents and two occupational therapists. Results: The inter-rater reliability of the weighted kappa between OTs and parents for the P-VFCS was 0.88 (95% confidence interval [CI], 0.62 to 0.89). The weighted kappa test-retest reliability for the P-VFCS was 0.91 (95% CI: 0.93 to 1.00) for occupational therapists and 0.90 (95% CI: 0.89 to 1.00) for parents. The face validity assessment revealed that 80% of parents of individuals with CP (8 out of 10) and 100% of occupational therapists (10 out of 10) found the P-VFCS suitable in translation and face validity quality. Conclusion: The findings indicated that the P-VFCS is a reliable and valid classification system for classifying visual functions in individuals with CP within clinical settings